ByzRev 07.2025.033: Maroula Perisanidi, Masculinity in Byzantium, c. 1000–1200:: Scholars, Clerics and Violence. Cambridge: Cambridge University Press 2024. - Constantinou, Stavroula (The Byzantine Review, 2025)
Maroula Perisanidi, Masculinity in Byzantium, c. 1000–1200: Scholars, Clerics and Violence. Cambridge: Cambridge University Press 2024. 206 pp. – ISBN 978-1-00949979-8